The Fermentum, the Celebration of Mass, and the Reception of the Eucharist in Early Fifth-Century Rome - Dyer, Joseph (Church history and religious culture, 2025)
In a letter to Bishop Decentius of Gubbio, Pope Innocent I (401–417) responded to a question about Roman use of the fermentum, a portion of consecrated bread from the pope’s Mass that was distributed each Sunday to priests celebrating Masses in the urban tituli. The fermentum was not brought to priests celebrating Mass in “parrochiae” and “cemeteries” outside the Wall of Rome. Innocent’s letter, supplemented by the evidence of the Ordines Romani, and donations of sacred vessels (the small calices ministeriales used for communion) by Constantine and the popes, testifies to the frequent reception of communion and the frequency of Mass in urbe and extra muros.